Management of Shweta Pradar (Leucorrhoea)through Ayurveda A Single Case Study - Mahmood, Sufia; Nematullah, Md; Ghosh, Sukumar (International Research Journal of Ayurveda & Yoga, 2022)
Shweta Pradar i.e. Leucorrhoea, commonly known as vaginal discharge is one of the important major issues experienced in gynecological practice. It is usual to experience some white discharge. Leucorrhoea is a condition in which there is an excessive amount of white discharge from the vaginal area as a result of inflammation or infection of the lower genital tract, which causes discomfort. Physiologically or pathologically, the symptom can affect people of any age. The vulnerable are those with a low socioeconomic status. Most women of all ages have dealt with it, especially when they are of child bearing or reproductive age. As in our country due to poor nutrition, multiple childbirth, low socioeconomic status, poverty, population growth, negligence of proper hygiene, many women are anaemic, malnourished, ill-health may suffer from such infection. It is important to treat Shweta Pradar (leucorrhoea) as soon as possible because it might lead to major complications if not treated. For abnormal white vaginal discharges, the word "Shweta Pradar" has been described in Ayurveda and it is extensively discussed in Ayurvedic texts. Due to kapha and Vata Doshadhikya, this symptom appears. However, according to Charak Samhita, Kapha is the primary Dosha that causes leucorrhoea. In this case report, a 24-year-old female patient with Shweta Pradar has complained of white discharge for the past nine months, along with katisula (low back ache), Daurbalya (weakness), Kandu (itching), Durgandha (odour), and occasionally Daha (burning sensation). She was treated by Shamana Chikitsa (palliative treatment) and Yoni Prakshalana for one month. She got excellent relief in symptoms by above treatment.